Clinical Indications Of Chandraprabha Vati An Experiential And Scientific View - Shripathi , Acharya G; Acharya, Miss Rajeshwari S (International Research Journal of Ayurveda & Yoga, 2021)
Herbo mineral formulations are becoming popular in the current medical practice and are often used by Ayurveda physicians. Pravala panchamrita rasa, mrityunjaya rasa, Agnitundi vati, yogaraja guggulu , Kaishora guggulu , Sootashekhara rasa, Swasakuthara rasa, and Makaradhwaja vati are few such formulations which are used in both acute and chronic and especially in non-communicable disorders . There are least side effects even after prolonged usage of these drugs. Chandraprabha vati is one such Herbo mineral formulation which is used especially in gynae disorders, urinary disorders and in pain management. Apart from some herbal drugs, mineral drugs like Swarna makshika Bhasma , Shilajatu and Guggulu are main ingredients in this formulation . Apart from disease specific usage, it can also be used to increase Hb %, it is useful as Vayasthapana, rasayana and antiaging also.[1][2][3] The present paper highlights about the clinical indications of Chandraprabha vati in an experiential and scientific view.